3(x+2)-9=28

Simple and best practice solution for 3(x+2)-9=28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-9=28 equation:


Simplifying
3(x + 2) + -9 = 28

Reorder the terms:
3(2 + x) + -9 = 28
(2 * 3 + x * 3) + -9 = 28
(6 + 3x) + -9 = 28

Reorder the terms:
6 + -9 + 3x = 28

Combine like terms: 6 + -9 = -3
-3 + 3x = 28

Solving
-3 + 3x = 28

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 3x = 28 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = 28 + 3
3x = 28 + 3

Combine like terms: 28 + 3 = 31
3x = 31

Divide each side by '3'.
x = 10.33333333

Simplifying
x = 10.33333333

See similar equations:

| -1+4x=-33 | | 6m+1=25 | | 7(x-2)=12+7x | | -3x+3-7x=53 | | 2k^2-250=0 | | 7x+25=-25 | | 247=x | | 1/9-1 | | x^2+7x=x+16 | | (6m-5)(m+3)=0 | | 6((-5)-9)+4((-5)-6)+23(-5)+9= | | 3x/2-4=6 | | y^5=16y^3 | | 3x+9-2(x+5)=4x-2(3-x) | | (y-9)(y-6)=0 | | 10y-3=-8-4y | | 2x^2=1-5 | | Y=-5+-3X | | (m+1)x=a-1 | | 2(3X+4)-2X=7X-3(-2X+11) | | -6(-1-3x)=96 | | 5/5/6-3/1/3 | | T(n)=100n+5 | | 87(-5)+9(9(-5)-4)= | | -2(8+6x)=-40 | | x^2+38x+3=0 | | (x-3)2+(y-5)2=81 | | 54/9=n/7 | | 21=d | | -105+4(-2(2)+3(-5))+8(2)= | | 3000=2X*X/2 | | -4(6x+2)=280 |

Equations solver categories